Reconsidering the water system of Roman Barcino (Barcelona) from supply to discharge - Orengo, Hèctor A.; Miró i Alaix, Carme (Springer, 2013)
This paper presents the results of the ‘Roman Barcino Water Network’ Project. This study employed a series of methodologies aiming at joining and interpreting all data available on water supply, distribution, management, use and discharge in the Romancolony of Barcino (modern Barcelona). Analyses of the results substantially modified previous knowledge of Barcino’s water organization and provided one of the few examples in which the whole water system of a Roman city has been tackled. We concluded that the water supply employed a single aqueduct, which divided before entering the city and not two of them as it was previously assumed. Barcino’s water distribution system was designed according to the different uses of water and was conditioned by the city’s particular topography. The results also stress the colony’s ample water availability, which despite its small size, allowed the maintenance of multiple public and private baths as befitted an accommodated population of merchants and administrators.